Study on the Potential of Waste in Pangkalpinang as Source of Power Generation - Welly Yandi; Sunanda, Wahri; Fitsa Alfazumi , Nada (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
The Waste Power Plant is one of the power plants with a new renewable energy concept that utilizes waste as fuel. The processing of waste into electrical energy is carried out in two ways: the thermal conversion process and the biological conversion process to find the potential for waste that can be used as fuel to generate electricity. The analysis is needed, especially for Pangkalpinang, which currently has a lot of unprocessed waste. This research was conducted through calculations using several formulas that have been used in previous studies. From these results, the potential waste in 2015 is 97.25 tons/day and produces energy of 18548.10 MWh/year, and in 2020, it was about 186.57 tons/day and produced energy of 35547.18 MWh/year. The projection calculations are carried out to determine the potential for 2021 to 2030. Waste as much as 182523 tons/day in2021 can produce energy of as much as 34776.11 MWh/year. And in 2030, the amount of waste as much as 218132 tons/day can generate an energy potential of 41560.69 MWh/year.